Joshua’s profile at the descent from Mount Sinai - Štrba, Blažej (Liber annuus, 2022)
The pericope of Exod 32:15-19 proves that Joshua descended with Moses from the Mountain of God. Scholars generally explain Joshua’s descent minimalistically, i.e. Joshua was not in the camp, and thus from the perspective of the people’s idolatry, his profile remains unstained. Only recently has the view emerged that the privilege of accompanying Moses as his assistant is more important than merely being disassociated from idolatry. Similarly, Joshua’s first words about the sound of war in the camp (v. 17), are often considered as indicative of both Joshua’s military experience and his misinterpretation of the event. In their interpretations, Joshua dominates only as a military leader. However, the lacuna about Joshua’s whereabouts during Moses’ stay on the mountain can be explained differently, in Joshua’s favour without obscuring Moses’ role in communicating with the LORD. The text seems to present Joshua, Moses’ personal assistant, as a careful listener. Moreover, he seems to be the only speaker during the descent (v. 18) and not Moses as it is usually interpreted, and he was able to recognize the singing as cultic. All in all, Joshua’s image seems to reflect later postexilic redactional influence that highlighted him as a prudent assistant of Moses.